Class clown fish - Sherry, Kevin; Dzioba, Wes. (New York, NY : Graphix/Scholastic, 2021)
"When a silly prank lands Squizzard in deep trouble, he comes down with a case of the barnacle blues. Instead of going to the Coral Carnival with his friends, he'll have to do the swim-possible and turn Seaweed Elementary's junk-filled basement into an activity room for after-school clubs. But there just may be hidden treasures to discover if Squizzard can stop all the funny business long enough to find them..."--Back cover.
4-8
GN 300
Accelerated Reader AR
Keywords: Squids -- Fiction; Marine animals -- Fiction; Friendship -- Fiction; Conduct of life -- Fiction; Practical jokes -- Fiction; School stories; Graphic novels; Graphic novels